Welcome to the wicked wax museum - Stine, R. L. (New York : Scholastic, 1996)
Reader experiences the adventures of visiting a wax museum, where things are not what they seem. Use the clues and decide your own fate.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
RL: 4.
008-012.
470
470
Keywords: Plot-your-own stories -- Juvenile fiction; Horror tales